How relative performance information affects employee behavior: a systematic review of empirical research. Issue 1 (6th December 2021) - Schnieder, Christian
Abstract : Purpose: This paper provides an overview of the empirical findings on how relative performance information (RPI) affects employee behavior. Additionally, the review identifies future research opportunities based on a systematic analysis of the literature that incorporates findings across several disciplines and provides replicable, extensive coverage. Design/methodology/approach: This paper addresses a research gap via synthesis, drawing on the empirical literature identified and analyzed systematically. A conceptual framework is developed to integrate the studies. Findings: The effect of RPI on performance through enhanced effort is positive; moreover, publicity and performance-dependent compensation strengthen the effect. However, RPI has also been found to increase sabotage among employees, and it can lead to less honest reporting. Future research could examine critical mediators and moderators of the RPI-performance relationship and thus complement the findings. Additionally, the effects of group-based RPI remain underrepresented. Future work could help to assess in greater detail how RPI interacts with culture and norms and whether RPI is due to personal expectations. There is also room for further research regarding the effects of RPI on cooperation, its consequences for learning, how it affects budgeting decisions and its implications for risk taking. Originality/value: This paper presents the first literature review in the field of RPI. It provides synthesized knowledge about whether RPI is beneficial or detrimental to organizational performance.